Perspektif Ekologi Politik Kebijakan Pengelolaan Danau Limboto - Hasim Hasim (Publik, 2018)
The Limboto Lake is the largest lake in Gorontalo Province. These natural resources have biodiversity of fishery which become economic source of coastal lake community. Besides, the economic activity of aquaculture fishery also grows rapidly in Limboto lake. The Limboto Lake is the largest lake in Gorontalo Province. These natural resources have biodiversity of fishery which become economic source of coastal lake community. Besides, the economic activity of aquaculture fishery also grows rapidly in Limboto lake ,The Limboto Lake has a strategic role for the province of Gorontalo. The Limboto lake degradation shows a more destructive of the area and the depth is reduced. This research study the product of law as a environmental politic instrument of the government and analyzes it in a political ecological perspective. The research design used descriptive quantitative and qualitative by using methodological approach of political ecology. The results show that regulation related to general management of the lake and Lake Limboto is particularly weak in the context of cohesiveness, harmonization, and problem focus.